The effect of comonomer styrene on the grafting of maleic anhydride onto cyclized natural rubber - Siregar, Muhammad Said; Ardilla, Desi; Eddiyanto, Eddiyanto; Nasution, Asmarasari (Jurnal Pendidikan Kimia, 2024)
The grafting degree of maleic anhydride onto cyclized natural rubber is generally still low. This is due to the lack of electron density of the maleic anhydride double bond so that its reactivity is low. This research aims to increase the grafting degree by the addition of a styrene comonomer. Grafting of maleic anhydride onto cyclized natural rubber had been performed in an internal mixer 150 oC and 80 rpm in the presence of styrene comonomer. The grafted product was analyzed by Fourier Transform Infra-Red to determine the presence of maleic groups and Differential Scanning Calorimetry and Thermalgravimetric to investigate its thermal properties. Fourier Transform Infra-Red spectra confirmed that the grafted product of maleic anhydride onto Cyclized Natural Rubber formed with absorption at 1700 cm-1, 1850 cm-1 and 700 cm-1. The higher concentration of maleic anhydride reacted the higher of grafting degree of maleic anhydride with the high intensity of absorption at 1700 cm-1 and 1850 cm-1. Differential Scanning Calorimetry spectra showed that the glass transition temperature of maleated Cyclized Natural Rubber products increases, the more comonomer are added the higher the glass transition temperature of the product. Generally, based on the Thermalgravimetric spectra, the thermal properties of grafted product does not change significantly compared to the blank sample.